2010
DOI: 10.1158/0008-5472.can-10-1169
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated Na+ Channel SCN5A Is a Key Regulator of a Gene Transcriptional Network That Controls Colon Cancer Invasion

Abstract: Voltage-gated Na + channels (VGSC) have been implicated in the metastatic potential of human breast, prostate, and lung cancer cells. Specifically, the SCN5A gene encoding the VGSC isotype Na v 1.5 has been defined as a key driver of human cancer cell invasion. In this study, we examined the expression and function of VGSCs in a panel of colon cancer cell lines by electrophysiologic recordings. Na + channel activity and invasive potential were inhibited pharmacologically by tetrodotoxin or genetically by small… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
280
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(293 citation statements)
references
References 48 publications
12
280
1
Order By: Relevance
“…In the case of MDA-MB-231 and MDA-MB-468 cells, the sigma-1 receptor translocates nNa v 1.5 protein to the plasma membrane and reduces adhesion, thereby enhancing the metastatic potential. These effects are consistent with the interaction occurring early in metastasis and, indeed, House et al (2010) have shown that VGSC expression is upstream of a network of genes controlling the invasiveness in colon cancer. Studies of Kv11.1 (hERG) and sigma-1 receptor are also consistent with the idea of sigma-1 receptor behaving either like a chaperone and/or a channel regulatory auxillary subunit through protein-protein interaction (Crottes et al 2011;Kinoshita et al 2012).…”
Section: Conclusion and Future Perspectivessupporting
confidence: 86%
See 1 more Smart Citation
“…In the case of MDA-MB-231 and MDA-MB-468 cells, the sigma-1 receptor translocates nNa v 1.5 protein to the plasma membrane and reduces adhesion, thereby enhancing the metastatic potential. These effects are consistent with the interaction occurring early in metastasis and, indeed, House et al (2010) have shown that VGSC expression is upstream of a network of genes controlling the invasiveness in colon cancer. Studies of Kv11.1 (hERG) and sigma-1 receptor are also consistent with the idea of sigma-1 receptor behaving either like a chaperone and/or a channel regulatory auxillary subunit through protein-protein interaction (Crottes et al 2011;Kinoshita et al 2012).…”
Section: Conclusion and Future Perspectivessupporting
confidence: 86%
“…Several studies have shown that functional VGSC expression occurs in a variety of carcinomas and promotes metastatic behaviour. Such carcinomas include BCa as well as cancers of the prostate (Grimes et al 1995;Laniado et al 1997;Nakajima et al 2009), lung (Onganer and Djamgoz 2005;Campbell et al 2013), colon (House et al 2010) and cervix (Diaz et al 2007). It has been suggested, therefore, (1) that VGSC up-regulation is an early event in metastatic progression and (2) that VGSC expression is a 'switch,' necessary and sufficient for engaging cancer cells in a highly invasive state.…”
mentioning
confidence: 99%
“…Metastasis is a process where cells escape from a primary tumor, enter circulation (blood or lymph), migrate and invade other tissues, proliferate and form secondary tumors. In in vitro experiments, it has been shown that VGSCs are associated to proliferation, motility, and invasion of breast, lung, ovary and prostate cancer (Roger et al, 2003;Gao et al, 2010;Diss et al 2005;Chioni et al, 2010;Roger et al, 2007;House, et al, 2010;Bennett et al, 2004). In prostate cancer cells, the main VGSC overexpressed is the Na V 1.7 subunit, while in breast, colon and ovary the Na V 1.5 subunit is the predominant subunit overexpressed.…”
Section: Sodium Channelsmentioning
confidence: 99%
“…They are blocked by the highly specific blocker tetrodotoxin (TTX) at different doses from nM to µM concentrations depending on isoforms and numerous pharmacological modulators of these channels have been developed by pharmaceutical companies for the treatment of pain or some cardiovascular diseases. The expression and activity of pore-forming alpha subunits of NaV have been linked to cancer cell migration/invasion originating from different tissues such as prostate (Diss et al, 2001), breast (Fraser et al, 2005;Gillet et al, 2009;Roger et al, 2003), lung (Onganer & Djamgoz, 2005;Roger et al, 2007), cervix (Diaz et al, 2007), colon (House et al, 2010), ovaries (Gao et al, 2010). Depending on the tissues, pore-forming isoforms responsible for the Na+ current and for the cellular effect, i.e.…”
Section: Voltage-gated Sodium Channel Nav16mentioning
confidence: 99%